Carbon supported NiRu nanoparticles as effective hydrogen evolution catalysts for anion exchange membrane water electrolyzers. (1st October 2022) - Ruck, S; Körner, A; Hutzler, A; Bierling, M; Gonzalez, J; Qu, W; Bock, C; Thiele, S; Peach, R; Pham, C V
Abstract: Establishing anion exchange membrane water electrolysis (AEMWE) as a new technology for efficient hydrogen production requires cost-effective and high-performance catalyst materials. Here, we report the synthesis and comprehensive characterization of carbon supported NiRu alloy nanoparticles as a cost-effective hydrogen evolution reaction catalyst for AEMWEs. Different NiRu catalysts were synthesized using a facile and scalable impregnation method. Half-cell results showed the 'NiRu' catalyst with ca. 10 wt.% Ru to exhibit an increased noble metal mass activity and slightly decreased Tafel slope compared to a commercial Pt/C catalyst with 60 wt.% Pt. Further, we report the application of NiRu/C as a cathodic catalyst in AEMWE full cell for the first time. In full cell tests, the synthesized catalysts exhibit 2 A cm −2 at 1.95 V with a low loading of 0.1 mgPGM cm −2 at the cathode.